Decompression and reconstruction the spinal TB lesion of a single vertebra through thoracoscopy alone or combined with foraminal endoscopy - Neng Ru; RuiYang Wang; Jie Liang; FeiFan Wang; Fan Zhang; Qing Liu; ChangJin Guo; Yu Wu (Journal of Orthopaedic Surgery and Research)
Abstract Objective This study aimed to compare the clinical efficacy of thoracoscopy combined with transforaminal endoscopy and thoracoscopy alone in the treatment of thoracic tuberculosis. Methods Patients with thoracic tuberculosis who visited our hospital from February 2018 to October 2022 were retrospectively analyzed. The patients were divided into thoracoscopic combined transforaminal endoscopic surgery group (group A) and thoracoscopic surgery alone group (group B) according to the surgical methods. Surgery-related information, VAS score, ODI score, degree of spinal cord function improvement, fusion time, and progression of kyphotic deformity were compared. Results A total of 37 patients were included, 16 in group A and 21 in group B. Postoperative follow-up time was 10–48 months, with an average of 28.62 ± 10.53 months. All patients had significant improvement in chest and back pain and spinal cord function after the operation. There were statistical differences in operation time, intraoperative blood loss, incidence rate of complications, and JOA score at 1 week and 3 months after operation between the two groups (P<0.05). There was no significant difference in VAS, ODI score, kyphotic angle correction, kyphotic correction loss angle, postoperative drainage volume, and fusion time between the two groups (P>0.05). All patients had no recurrence of thoracic tuberculosis during follow-up. Conclusion Thoracoscopy combined with transforaminal endoscopy produce equivalent long-term results with shorter operation time, less intraoperative blood loss, less complications and higher surgical safety comparing to thoracoscopy alone. And thoracoscopy combined with transforaminal endoscopy can fully decompress and facilitate the early recovery of spinal cord function.